2021
DOI: 10.3390/biom11050685
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibulins in Embryonic Stage Development and Their Involvement in Various Diseases

Abstract: The extracellular matrix (ECM) plays an important role in the evolution of early metazoans, as it provides structural and biochemical support to the surrounding cells through the cell–cell and cell–matrix interactions. In multi-cellular organisms, ECM plays a pivotal role in the differentiation of tissues and in the development of organs. Fibulins are ECM glycoproteins, found in a variety of tissues associated with basement membranes, elastic fibers, proteoglycan aggregates, and fibronectin microfibrils. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 144 publications
(185 reference statements)
1
14
0
Order By: Relevance
“…Our work has identified EGFDs in human fibulins as substrates of AspH-catalyzed asparagine hydroxylation in the ovary, an observation which is of interest considering the importance of fibulins in extracellular matrix biochemistry, including their proposed roles in cancer biology ( 80 , 84 ). Fibulins might be relevant AspH downstream targets transmitting pathophysiologic-relevant effects of AspH upregulation in some cancer cells.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our work has identified EGFDs in human fibulins as substrates of AspH-catalyzed asparagine hydroxylation in the ovary, an observation which is of interest considering the importance of fibulins in extracellular matrix biochemistry, including their proposed roles in cancer biology ( 80 , 84 ). Fibulins might be relevant AspH downstream targets transmitting pathophysiologic-relevant effects of AspH upregulation in some cancer cells.…”
Section: Discussionmentioning
confidence: 89%
“…This approach has been found to improve the identification of hydroxylated proline residues by a factor of ∼9 when compared to use of the MaxQuant software (Max-Planck-Institute of Biochemistry; https://maxquant.org ) ( 78 ). We chose to investigate data from female reproductive tissue as these generally contain high levels of AspH and EGFD-containing proteins that are putative AspH substrates ( 53 , 79 , 80 , 81 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 50 IPM as an intensity threshold, we focused on proteins that were relatively abundant (≥50 IPM) in the EVs derived from all the PDAC cell lines with >1.5-fold increase in expression compared with HPDE cells. Among the 36 proteins identified, a set of 8 proteins (alpha-2-HS-glycoprotein, 78 apolipoprotein E, 79,80 fibulin-1, 81 aminopeptidase N [ANPEP or CD13], 82 plasminogen, 83 gelsolin, 84 S100-A4, 79 and pigment epithelium-derived factor 84 ) that were previously found to be associated with PDAC is shown in Figure 7. Except for ANPEP (CD13), the remaining proteins showed increased expression in the EVs secreted from PDAC and CAF cell lines relative to HPDE.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, all cases with identified variants had poor surgical outcomes and ended with liver cirrhosis and liver failure. The results of the survival analysis, which showed better native liver survival in BA with the recessive genotype of rs6761893 suggested that EFEMP1 variants might have some defects in biliary tract remodeling during embryonic period 17 or extracellular matrix dysregulation which may results in decreased bile excretion 18 . Although clear explanation about EFEMP1 functions is beyond the scope of our study, these findings indicate that EFEMP1 is an interesting candidate gene that should be further explored for its role in the pathogenesis and severity factor of BA.…”
Section: Discussionmentioning
confidence: 99%